2016
DOI: 10.1007/s00234-016-1644-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between neuromelanin-sensitive MR imaging and 123I-FP-CIT SPECT in patients with parkinsonism

Abstract: Decrease of the high signal intensity region of the SNc on neuromelanin-sensitive MRI would indicate damage to the nigrostriatal dopaminergic function as well as loss of dopaminergic neurons. We conclude that neuromelanin-sensitive MRI is a useful diagnostic biomarker for parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
5
31
1
Order By: Relevance
“…Compared to age‐matched controls, PD patients showed reduced volume and contrast‐to‐noise‐ratio of the SNc, and both measurements, though SNc volume more than contrast ratio, showed a positive correlation with the corresponding striatal 123 I‐FP‐CIT binding. A similar significant correlation between SNc volume and striatal specific binding ratio of 123 I‐FP‐CIT has been reported in a cohort of 23 patients with parkinsonism (17 PD, 3 MSA, 1 PSP, 1 spinocerebellar degeneration, and 1 ET) . Taken together findings from these two studied suggest that loss of nigral neuromelanin is directly associated with loss/dysfunction of striatal dopamine presynaptic terminals and can be potentially used as a biomarker of nigrostriatal dysfunction.…”
Section: Neuromelanin Sensitive Mrisupporting
confidence: 78%
“…Compared to age‐matched controls, PD patients showed reduced volume and contrast‐to‐noise‐ratio of the SNc, and both measurements, though SNc volume more than contrast ratio, showed a positive correlation with the corresponding striatal 123 I‐FP‐CIT binding. A similar significant correlation between SNc volume and striatal specific binding ratio of 123 I‐FP‐CIT has been reported in a cohort of 23 patients with parkinsonism (17 PD, 3 MSA, 1 PSP, 1 spinocerebellar degeneration, and 1 ET) . Taken together findings from these two studied suggest that loss of nigral neuromelanin is directly associated with loss/dysfunction of striatal dopamine presynaptic terminals and can be potentially used as a biomarker of nigrostriatal dysfunction.…”
Section: Neuromelanin Sensitive Mrisupporting
confidence: 78%
“…Sasaki et al . reported that the paramagnetic T1 shortening area in NM‐MRI was clearly correlated with NM‐SNc in gross specimens, suggesting that the high signal intensity areas corresponded to NM‐containing neurons . Colloby et al .…”
Section: Discussionmentioning
confidence: 96%
“…Previous neuropathological studies reported an association between the number of surviving NM‐containing neurons and the functional state of those neurons’ axon terminals . Therefore, NM‐SNc may predict not only the number of dopaminergic neurons but also the terminal function . Furthermore, PD pathology occurs asymmetrically and motor symptoms manifest unilaterally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations